GENERAL LEGAL OVERVIEW ON THE SYSTEM OF PRIVATE PRISONS (Law and world, 2019)
Criminal law is the most ancient and classical branch of the law. There is no doubt that elementary, simple norms of criminal law existed even in primitive society.1 Main speciﬁc of criminal law is that, generally this branch of law is connected with two main notions: crime and punishment. It can be said that this two main notions create some sort of judicial results in criminal law. These two notions are closely related with each other: there is no punishment without crime and there should be no crime without punishment. Of course, right on punishment is exclusive monopoly right of state.2 In modern judicial literature is often mentioned that criminal law is, “last resort”. 3 Usually, the most important values (ex. life, health, personal inviolability etc) are reserved by criminal law. These values are not only important for separate individuals, but also for whole society. So, when these interests are at risk state should take appropriate measures: make full investigation and use criminal responsibility on persons who are threatening above mentioned important interests.